2014
DOI: 10.1055/s-0034-1390770
|View full text |Cite
|
Sign up to set email alerts
|

Polyglycolic acid sheet application to prevent esophageal stricture after endoscopic submucosal dissection for esophageal squamous cell carcinoma

Abstract: PGA sheets may have the potential to prevent esophageal stricture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
97
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(98 citation statements)
references
References 13 publications
0
97
1
Order By: Relevance
“…Sakaguchi et al [13] reported the usefulness of polyglycolic acid (PGA) sheets with fibrin glue in the prevention of esophageal stricture after ESD. In line with this, another report showed that the percentage of postoperative stricture after application of PGA sheets was 7.7% in patients with a mucosal defect covering greater than seven-twelfths of the esophageal circumference [14] . Furthermore, Kataoka et al [15] reported a case in which esophageal stricture was successfully prevented by endoscopic TA injection followed by the application of PGA sheets after a whole-circumferential resection.…”
Section: Discussionmentioning
confidence: 57%
“…Sakaguchi et al [13] reported the usefulness of polyglycolic acid (PGA) sheets with fibrin glue in the prevention of esophageal stricture after ESD. In line with this, another report showed that the percentage of postoperative stricture after application of PGA sheets was 7.7% in patients with a mucosal defect covering greater than seven-twelfths of the esophageal circumference [14] . Furthermore, Kataoka et al [15] reported a case in which esophageal stricture was successfully prevented by endoscopic TA injection followed by the application of PGA sheets after a whole-circumferential resection.…”
Section: Discussionmentioning
confidence: 57%
“…Once stricture occurs, repeated endoscopic balloon dilation (EBD) is required, which can decrease the patient’s quality of life. The efficacy of prophylactic steroids and polyglycolic acid (PGA) sheets for the prevention of esophageal stricture has been reported [6-8]. …”
Section: Introductionmentioning
confidence: 99%
“…Mucosal transplantation to the ESD wound is an effective and safe measure, but the technique remains underdeveloped and has cost implications [11]. Other preventive options for stricture mainly referring to local treatments of topical hemostatic powder and poly eth- anol acid membrane still lack sound evidence [12][13][14]. Furthermore, the interventions mentioned above have limited efficacy for the prevention of esophageal stricture after ESD.…”
Section: Discussionmentioning
confidence: 99%